2018
DOI: 10.1016/j.scriptamat.2018.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Fine (Cr,Fe)2B borides on grain boundaries in a 10Cr–0.01B martensitic steel

Abstract: A 10Cr creep resistant martensitic steel with 108 ppm B was normalized at 1100°C for 1h and air cooled. Fine (Cr,Fe) 2 B borides were observed on the majority of prior austenite grain boundaries, all of which were high angle boundaries, as revealed by EBSD-based reconstruction of parent austenite grains. Some high angle boundaries including twin boundaries were boride-free. Segregation of boron to austenite grain boundaries during slow cooling from 1100⁰C led to boride nucleation and growth. Their size increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…Tiny particles are apparent in the matrix and on the front of boride columns. These tiny boride particles are generally present at high-angle prior-austenitic grain boundaries [4].…”
Section: Phase Analysis Microstructure and Hardnessmentioning
confidence: 99%
See 2 more Smart Citations
“…Tiny particles are apparent in the matrix and on the front of boride columns. These tiny boride particles are generally present at high-angle prior-austenitic grain boundaries [4].…”
Section: Phase Analysis Microstructure and Hardnessmentioning
confidence: 99%
“…Boronizing, a thermo-chemical treatment, is accompanied by the controlled diffusion of boron into the metal surface producing different phases of metal borides (M-B, M = Fe, Cr, Ti, Ni, V, Mo, Mn, W, etc.) [4][5][6][7][8][9][10][11][12][13][14]. A considerable improvement in the quality of the surface layer is possible through combining the boronizing treatment with other surface treatments (like borocaburising, laser treatment on the boronized surface, etc.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5e), which has an even higher evaporation field, the wide B profile seems to partially reflect the real B distribution. APT has been proven to be a very powerful tool for understanding the mechanisms of B segregation (e.g., Li et al, 2015; Fedorova et al, 2017, 2018; Miyamoto et al, 2018), however, remarkable discrepancies were found between the experimental results and theoretical prediction, thus further work combining experiment and theory is required to gain a better understanding.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is possible to obtain a material whose properties have lesser decrease in ductility and impact toughness as the boron content increases compared with similar boron-containing cast/wrought borated stainless steels. The application of boron in powder metallurgy as addition to ferrous alloys has been of interest to numerous researchers over the last years [3][4][5][6][7][8][9][10][11][12]. The main cause of this interest is the eutectic reaction between iron and boron, resulting in the appearance of a liquid phase which efficiently improves mass transport by intensifying a diffusion process [7].…”
Section: Introductionmentioning
confidence: 99%